Impact of BCR-ABL mutations on patients with chronic myeloid leukemia - Hochhaus, Andreas; La Rosée, Paul; Müller, Martin Christian; Ernst, Thomas; Cross, Nicholas C.P. (Cell cycle, 2011)
Therapies that target BCR-ABL in chronic myeloid leukemia, including imatinib, dasatinib and nilotinib, have dramatically improved patient outcome. BCR-ABL mutations, however, contribute to treatment resistance by disrupting drug contact sites or causing conformational changes thus making contact sites inaccessible. Clinical data indicate that developing BCR-ABL mutations during imatinib treatment is predictive for shorter progression-free survival, and that outcomes may depend on mutation type or location. In vitro, dasatinib and nilotinib inhibit most imatinib-resistant BCR-ABL mutations, except for T315I. In clinical studies, other mutations associated with treatment resistance include V299L, T315A, and F317I/L for dasatinib and Y253F/H, E255K/V, and F359C/V for nilotinib. Evaluating patients with clinical signs of resistance for BCR-ABL mutations is an important component of disease monitoring, potentially facilitating selection of subsequent therapy. First-line treatment with dasatinib or nilotinib instead of imatinib may reduce emergence of resistance but novel agents are needed to overcome the problematic T315I mutation.